Communication and culture. Proposals for the cross-cultural analysis of face-to-face communicative interactions. / Francisco Raga Gimeno. Madrid / Frankfurt. Iberoamericana / Vervuert, 2005, 277 pp. - Sales Salvador, Dora (2006)
This review does not present a summary.